Electrode for all-solid-state battery
By using imidazoline compounds to disperse fluoride solid electrolytes in composite particles, the resistance increase in all-solid-state batteries is mitigated, ensuring better long-term performance.
Patent Information
- Application Number
- JP2022116808
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-07-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-07-22
AI Technical Summary
The increase in resistance associated with long-term use of all-solid-state batteries is a significant challenge that needs to be addressed.
The use of imidazoline compounds as dispersants for fluoride solid electrolytes in composite particles within the electrodes, which enhances dispersibility and reduces the formation of aggregates, thereby minimizing the increase in resistance over time.
The incorporation of imidazoline compounds in the electrodes leads to improved dispersibility of active materials, reducing the rate of resistance increase and maintaining ion conduction paths, thus enhancing the battery's performance over time.
Smart Images

Figure 0007605794000006 
Figure 0007605794000001 
Figure 0007605794000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode for an all-solid-state battery. [Background technology]
[0002] JP2020-161364A discloses adding a dispersant to a composition for forming a solid electrolyte layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-161364 A Summary of the Invention [Problem to be solved by the invention]
[0004] There is a need to suppress the increase in resistance that occurs with long-term use. Therefore, an object of the present disclosure is to reduce the rate of increase in resistance. [Means for solving the problem]
[0005] 1. An electrode for an all-solid-state battery (hereinafter may be abbreviated as "electrode") includes 100 parts by mass of composite particles and more than 0 parts by mass and 0.3 parts by mass or less of an imidazoline-based compound (hereinafter may be abbreviated as "IM compound"). The composite particles include a core particle and a coating layer. The coating layer coats at least a portion of the surface of the core particle. The core particle includes an active material. The coating layer includes a fluoride solid electrolyte.
[0006] According to the new findings of the present disclosure, the dispersibility of the active material in the electrode can affect the increase in resistance that accompanies long-term use. The active material repeatedly expands and contracts during long-term use. The active material is a particle group. The particle group may not disperse, and may form an aggregate. In the aggregate, the volume change of the individual particles may accumulate. This may amplify the volume change of the aggregate. The surrounding ion conduction paths may not be able to keep up with the large volume change of the aggregate, and the ion conduction paths may be interrupted. It is believed that the interruption of the ion conduction paths promotes the increase in resistance.
[0007] Hereinafter, solid electrolyte may be abbreviated as "SE". For example, fluoride solid electrolyte may be abbreviated as "fluoride SE". In the electrode manufacturing process (slurry), the IM compound may act as a dispersant for the SE. According to the new findings of the present disclosure, the IM compound may impart high dispersibility, particularly to fluoride SE. The composite particles are coated with the fluoride SE. Therefore, the composite particles are less likely to aggregate and can be well dispersed in the electrode. That is, the active material is less likely to aggregate and can be well dispersed in the electrode. In addition, the fluoride SE tends to have a smaller increase in reaction resistance with long-term use than, for example, oxide SE (LiNbO3, etc.). The synergistic effect of these actions is expected to reduce the resistance increase rate.
[0008] However, if the blending amount of the IM compound is too large, the resistance increase rate may become higher. This is probably because the IM compound has insulating properties. Therefore, the blending amount of the IM compound has an upper limit (0.3 parts by mass).
[0009] 2. The electrode described in "1" above may contain, for example, 100 parts by mass of composite particles and 0.05 to 0.1 parts by mass of an imidazoline-based compound. This is because a reduction in the rate of increase in resistance is expected. The numerical range of "M to N" includes the upper and lower limits unless otherwise specified. For example, "0.05 to 0.1 parts by mass" indicates 0.05 parts by mass or more and 0.1 parts by mass or less.
[0010] 3. The electrode according to "1" or "2" above may further contain, for example, 10 to 100 parts by mass of a sulfide solid electrolyte. The sulfide SE can form an ion conduction path in the electrode. The sulfide SE can exhibit high ion conductivity.
[0011] 4. In the electrode according to any one of the above items "1" to "3", the imidazoline compound may be represented by, for example, the following formula (1).
[0012] [ka]
[0013] In the above formula (1), R 1 R is an alkyl group or a hydroxyalkyl group having 1 to 22 carbon atoms. 2 is an alkyl group or an alkenyl group having a carbon number of 10 to 22. The IM compound represented by the above formula (1) can impart high dispersibility to the fluoride SE.
[0014] 5. In the electrode according to any one of the above items "1" to "4", the fluoride solid electrolyte may be represented by, for example, the following formula (2). Li 3-x Ti x Al 1-x F6…(2) In the above formula (2), x satisfies 0≦x≦1. The fluoride SE represented by the above formula (2) tends to have a small increase in reaction resistance with long-term use.
[0015] 6. In the electrode according to any one of the above items "1" to "5", the ratio of the specific surface area of the composite particle to the specific surface area of the core particle may be greater than 1.07 and less than or equal to 3.27, since this is expected to enhance the effect of the IM compound.
[0016] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a conceptual diagram of an all-solid-state battery according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] <All-solid-state battery> FIG. 1 is a conceptual diagram of an all-solid-state battery in this embodiment. The all-solid-state battery 200 includes a power generating element 150. The all-solid-state battery 200 may include, for example, an exterior body (not shown). The exterior body may house the power generating element 150. The exterior body may be, for example, a pouch made of a metal foil laminate film, or a case made of metal. The all-solid-state battery 200 may include a single power generating element 150 alone, or may include a plurality of power generating elements 150. The plurality of power generating elements 150 may form, for example, a series circuit or a parallel circuit.
[0019] The power generating element 150 includes a first electrode 110, a separator layer 130, and a second electrode 120. The separator layer 130 is interposed between the first electrode 110 and the second electrode 120. The separator layer 130 separates the first electrode 110 from the second electrode 120. The separator layer 130 may include, for example, a sulfide SE (described later) or the like. The separator layer 130 may have a thickness of, for example, 1 to 100 μm.
[0020] The second electrode 120 has a different polarity from the first electrode 110. For example, when the first electrode 110 is a positive electrode, the second electrode 120 is a negative electrode. At least one of the first electrode 110 and the second electrode 120 includes composite particles and an IM compound. Hereinafter, the first electrode 110 and the second electrode 120 may be collectively referred to as "electrodes."
[0021] "electrode" The electrode includes an active material layer. The electrode may further include, for example, a substrate or the like. For example, the active material layer may be disposed on the surface of the substrate. The substrate may be, for example, sheet-shaped. The substrate may include, for example, an Al foil, a Cu foil, a Ni foil, or the like. The substrate may have a thickness of, for example, 5 to 50 μm.
[0022] The active material layer may have a thickness of, for example, 10 to 1000 μm. The active material layer includes composite particles and an IM compound. That is, the electrode includes composite particles and an IM compound. The active material layer may further include an auxiliary material. The auxiliary material may include, for example, at least one selected from the group consisting of an ion conductive material, an electron conductive material, and a binder.
[0023] (Imidazoline compounds) The IM compound can impart high dispersibility to the fluoride SE. That is, the IM compound can impart high dispersibility to the composite particles. The IM compound has an imidazoline skeleton. The imidazoline skeleton includes a nitrogen-containing heterocyclic structure. The imidazoline skeleton can be derived from imidazole. The IM compound may be represented by, for example, the following formula (1).
[0024] [ka]
[0025] In the above formula (1), R 1 R may be, for example, an alkyl group or a hydroxyalkyl group. 1may have, for example, 1 to 22 carbon atoms. In the hydroxyalkyl group, for example, a hydroxyl group may be bonded to the terminal carbon atom opposite to the carbon atom bonded to N (nitrogen atom). R 2 R may be, for example, an alkyl or alkenyl group. 2 may have, for example, a carbon number of 10 to 22. In the alkenyl group, the position and number of double bonds are optional.
[0026] The IM compound may include, for example, 1-hydroxyethyl-2-alkenylimidazoline. The active material layer may include one type of imidazoline compound alone, or may include two or more types of imidazoline compounds. For example, "DISPERBYK (registered trademark)-109" manufactured by BYK-Chemie includes 1-hydroxyethyl-2-alkenylimidazoline.
[0027] The amount of the IM compound is more than 0 parts by mass and not more than 0.3 parts by mass per 100 parts by mass of the composite particles. If the amount of the IM compound exceeds 0.3 parts by mass, the resistance increase rate may be higher. The amount of the IM compound may be, for example, 0.05 to 0.103 parts by mass, 0.05 to 0.1 parts by mass, or 0.103 to 0.2 parts by mass per 100 parts by mass of the composite particles. When the amount of the IM compound is 0.05 to 0.1 parts by mass per 100 parts by mass of the composite particles, the resistance increase rate tends to be lower.
[0028] (composite particles) The composite particle includes a core particle and a coating layer. The D50 of the composite particle may be, for example, 1 to 30 μm. "D50" indicates the particle diameter at which the cumulative frequency from the smallest size reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction particle size distribution measuring device. The composite particle may have any shape. The composite particle may be, for example, spherical, ellipsoidal, flake-like, or columnar. The term "particle" may also be used to mean a particle group or powder.
[0029] (covering layer) The coating layer covers at least a part of the surface of the core particle. The coating layer may cover the entire surface of the core particle. The coating layer may cover a part of the surface of the core particle. The thickness of the coating layer may be, for example, 5 to 50 nm.
[0030] The coating layer includes a fluoride SE. The fluoride SE may include, for example, Li and F. The fluoride SE may include, for example, at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr.
[0031] The fluoride SE may be represented, for example, by the following formula (2): Li 3-x Ti x Al 1-x F6…(2) In the above formula (2), x satisfies 0≦x≦1. For example, x may satisfy 0.2≦x≦0.8, 0.3≦x≦0.7, or 0.4≦x≦0.6.
[0032] (Core particle) The core particle is a base material of the composite particle. The composite particle may contain one core particle alone. The composite particle may contain a plurality of core particles. The core particle may be, for example, a secondary particle. The secondary particle is an aggregate of primary particles. The D50 of the secondary particle may be, for example, 1 to 30 μm. The average Feret's diameter of the primary particles may be, for example, 0.01 to 3 μm. The core particle may have any shape. The core particle may be, for example, spherical, ellipsoidal, flaky, or cylindrical.
[0033] The core particles contain an active material. The core particles may contain a positive electrode active material. That is, the electrode may be a positive electrode. The positive electrode active material may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, Li(NiCoMnAl)O2, and LiFePO4. For example, in "Li(NiCoMn)O2", "(NiCoMn)" indicates that the total of the composition ratios in the parentheses is 1. As long as the total is 1, the individual component amounts are arbitrary.
[0034] The positive electrode active material may be represented, for example, by the following formula (3). Li 1-y Ni x M 1-x O2…(3) 0.5 ≦ x ≦ 1, -0.5 ≦ y ≦ 0.5 In the above formula (3), M may contain, for example, at least one selected from the group consisting of Co, Mn, and Al. x may be, for example, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more.
[0035] The core particles may contain a negative electrode active material. That is, the electrode may be a negative electrode. The negative electrode active material may contain, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, hard carbon, Si, SiO x (0 < x < 2), Si-based alloys, Sn, SnO x (0 < x < 2), Li, Li-based alloys, and Li4Ti5O 12 and may contain at least one selected from the group consisting of.
[0036] (Method for forming composite particles) The composite particles may be formed by any method. For example, the composite particles may be formed by applying at least one type of mechanical energy selected from the group consisting of impact, compression, and shear to the processing target (a mixture of an active material and a fluoride SE). Examples of devices capable of the composite processing include "Nobilta" (manufactured by Hosokawa Micron Corporation) and "Balance Gran" (manufactured by Freund Turbo Corporation).
[0037] "Nobilta" comprises a cylindrical casing (container) and a rotor. The rotation axis of the rotor coincides with the central axis of the casing. As the rotor rotates at high speed inside the casing, energy due to impact, compression and shear can be imparted to the treatment object in the gap (clearance) between the inner wall of the casing and the rotor.
[0038] The "Balance Gran" includes a chopper and an agitator scraper. The chopper is arranged coaxially with the agitator scraper. The chopper promotes mixing and convection. The mixing and convection caused by the chopper are generated in a spiral shape from the outer periphery. The agitator scraper rotates in the opposite direction to the chopper. The chopper can impart energy to the processing object mainly by shearing.
[0039] (BET ratio) For example, the composite particles may be formed so that the specific surface area is increased compared to that of the active material (core particle). The "ratio of the specific surface area of the composite particles to the specific surface area of the core particle" is abbreviated as "BET ratio". The BET ratio may be, for example, 1.07 to 3.27, 1.16 to 3.27, 1.20 to 3.27, 1.50 to 3.00, 1.79 to 3.00, or 1.80 to 2.50. The larger the BET ratio, the more likely the effect of the IM compound is to increase. That is, when the BET ratio is large, a large dispersion effect can be expected with a small amount of IM compound added. By reducing the IM compound, for example, a reduction in initial resistance can be expected. For example, the BET ratio tends to be larger in the treatment with Balance Gran than in the treatment with Nobilta.
[0040] The "specific surface area" refers to the surface area per unit mass. The specific surface area can be measured by a specific surface area measuring device. For example, a specific surface area / pore distribution measuring device "Product name: BELSORP MINI" (or an equivalent product) manufactured by Microtrack-Bell may be used. The measurement procedure is, for example, as follows. 3 g of a measurement sample (powder) is placed in a measurement test tube. The measurement test tube is set in the specific surface area measuring device. A nitrogen gas adsorption test is performed in the specific surface area measuring device to obtain an adsorption isotherm. In the nitrogen gas adsorption test, the adsorption temperature is 77 K, and the upper limit of the adsorption relative pressure is 0.99 (P / P0). The specific surface area is obtained by analyzing the linear region of the adsorption isotherm by the BET method. The adsorption isotherm may be analyzed by analysis software (for example, "Product name: BELMaster7"). The specific surface area of the composite particle is, for example, 0.5 to 2 m 2 / g.
[0041] (Ion Conductive Material) The ion conductive material can form an ion conductive path in the active material layer. The ion conductive material may be, for example, particulate. The ion conductive material may have a D50 of, for example, 0.1 to 1 μm. The amount of the ion conductive material may be, for example, 10 to 100 parts by mass per 100 parts by mass of the composite particles.
[0042] The ion conductive material may include, for example, a sulfide SE. The electrode may include, for example, 10 to 100 parts by mass of a sulfide SE per 100 parts by mass of the composite particles. The sulfide SE may be, for example, a glass ceramic type or an argyrodite type. The sulfide SE may include, for example, Li, P, and S. The sulfide SE may include, for example, LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li2S-P2S5, Li4P2S6, Li7P3S 11 and Li3PS4.
[0043] For example, "LiI-LiBr-Li3PS4" indicates a sulfide SE produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio. For example, the sulfide SE may be produced by a mechanochemical method. The molar ratio may be specified by adding a number before each raw material (e.g., "LiI"). For example, "10LiI-15LiBr-75Li3PS4" indicates that the mixture is "LiI / LiBr / Li3PS4=10 / 15 / 75 (molar ratio)".
[0044] (Electronic Conductive Material) The electronic conductive material can form an electronic conductive path in the active material layer. The amount of the electronic conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles. The electronic conductive material may include, for example, at least one selected from the group consisting of acetylene black (AB), vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake (GF).
[0045] (Binder) The binder can bind solids together. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles. The binder may include, for example, at least one selected from the group consisting of styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), and vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP). EXAMPLES
[0046] <Sample preparation> No.1 (Preparation of negative electrode slurry) The following materials were prepared: Active material: Li4Ti5O 12 IM Compounds: 1-Hydroxyethyl-2-alkenylimidazolines Ion conductor: 10LiI-15LiBr-75Li3PS4 (D50=0.9μm) Electronic Conductive Material: VGCF Binder: SBR Dispersion medium: Tetralin
[0047] A slurry was prepared by mixing the active material, IM compound, ion conductive material, electronic conductive material, binder, and dispersion medium using an ultrasonic homogenizer (UH-50 manufactured by SMT). The solid content ratio was "active material / IM compound / ion conductive material / electronic conductive material / binder = 100 / 1.88 / 33.6 / 1.1 / 0.86 (mass ratio)". The solid content of the slurry was 58%.
[0048] (Preparation of composite particles) A Freund Turbo Balance Gran Model BG-25L was prepared. 95.4 parts by volume of the positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 O2) and 4.6 parts by volume of fluoride SE(Li 2.7 Ti 0.3 Al 0.7 The mixture of 1,2-dichlorophenyl phosphate (Pt) and 1,2-dichlorophenyl phosphate (F6) was subjected to a composite treatment to form composite particles. The treatment conditions were as follows:
[0049] Stirring speed: 1150rpm Processing time: 1 hour
[0050] (Preparation of Positive Electrode Slurry) The following materials were prepared: IM Compounds: 1-Hydroxyethyl-2-alkenylimidazolines Ion conductor: 10LiI-15LiBr-75Li3PS4 (D50=0.9μm) Electronic Conductive Material: VGCF, AB Binder: SBR Dispersion medium: Tetralin
[0051] A slurry was prepared by mixing the composite particles, IM compound, ion conductive material, electronic conductive material, binder, and dispersion medium using an ultrasonic homogenizer. The solid content ratio was "composite particles / IM compound / ion conductive material / VGCF / AB / binder = 100 / 0.05 / 32.38 / 3.11 / 0.308 / 0.431 (mass ratio)". The solid content of the slurry was 66.5%.
[0052] (Preparation of separator slurry) The following materials were prepared: Ion conductor: LiI-LiBr-Li2S-P2S5 (glass ceramic type, D50 = 2.5 μm) Binder solution: Solute SBR (mass fraction 5%), Solvent Heptane Dispersion medium: heptane
[0053] In a polypropylene container, the ion conductive material, the binder solution, and the dispersion medium were mixed for 30 seconds by an ultrasonic homogenizer. After mixing, the container was set on a shaker. The container was shaken by the shaker for 3 minutes to prepare a slurry.
[0054] (Preparation of power generating element) The slurry for the positive electrode was applied to the surface of a substrate (Al foil, 15 μm thick) using a blade applicator. After application, the slurry was dried for 30 minutes on a hot plate (set temperature 100° C.) to form an active material layer. In other words, a positive electrode was formed.
[0055] The negative electrode slurry was applied to the surface of a substrate (Ni foil, thickness 22 μm) using a blade applicator. After application, the slurry was dried for 30 minutes on a hot plate (set temperature 100° C.) to form an active material layer. That is, a negative electrode was formed. The weight of the negative electrode was adjusted so that the ratio of the specific charge capacity of the negative electrode to the specific charge capacity of the positive electrode (200 mAh / g) was 1.0.
[0056] The positive electrode was pressed. After pressing, the separator slurry was applied to the surface of the positive electrode using a die coater. After application, the slurry was dried for 30 minutes on a hot plate (set temperature 100°C) to form a separator layer. This completed the preparation of the first unit. The first unit was pressed using a roll press device. The linear pressure was 2 ton / cm.
[0057] The negative electrode was pressed. After pressing, the separator slurry was applied to the surface of the negative electrode using a die coater. After application, the slurry was dried for 30 minutes on a hot plate (set temperature 100°C) to form a separator layer. This completed the preparation of the second unit. The second unit was pressed using a roll press device. The linear pressure was 2 ton / cm.
[0058] The separator slurry was applied to the surface of a temporary support (metal foil). After application, the slurry was dried on a hot plate (set temperature 100° C.) for 30 minutes to form a separator layer.
[0059] The separator layer on the temporary support was transferred to the surface of the first unit. The planar shapes of the first unit and the second unit were adjusted by punching. The first unit and the second unit were laminated so that the separator layer of the first unit faced the separator layer of the second unit. This formed the power generation element. The power generation element was hot pressed using a roll press device. The pressing temperature was 160°C. The linear pressure was 2 ton / cm.
[0060] (Production of all-solid-state batteries) An exterior body (a pouch made of Al laminated film) was prepared. The power generating element was sealed in the exterior body. A restraining member was prepared. The restraining member was attached to the outside of the exterior body so that a pressure of 5 MPa was applied to the power generating element. Through the above steps, an all-solid-state battery was manufactured.
[0061] No.2~5 In the "preparation of slurry for positive electrode", electrodes and all-solid-state batteries were produced in the same manner as in No. 1, except that the blending amount of the IM compound was changed as shown in Table 1 below.
[0062] No.6 In the "Preparation of composite particles", electrodes and solid-state batteries were manufactured in the same manner as in No. 1, except that composite particles were formed by a "Nobilta model NOB-MINI" manufactured by Hosokawa Micron Corporation. The processing conditions were as follows:
[0063] Clearance between casing and rotor: 2mm Rotational speed: 6100 rpm Processing time: 30 minutes
[0064] <Evaluation> The SOC (State Of Charge) of the solid-state battery was adjusted to 80%. The solid-state battery was discharged for 2 seconds at an hourly rate of 46.4C in a thermostatic chamber (set temperature 25°C). The initial resistance was calculated from the voltage drop during discharge and the current. Note that "C" is the symbol for the hourly rate of current. At an hourly rate of 1C, the rated capacity of the battery is discharged in 1 hour. After measuring the initial resistance, a durability test was conducted. In other words, a high-temperature storage test was conducted under the following conditions:
[0065] Test temperature: 60℃ SOC at start of save: 80% Storage time: 168 hours
[0066] After the durability test, the post-durability resistance was measured in the same manner as the initial resistance. The resistance increase rate was calculated by dividing the post-durability resistance by the initial resistance.
[0067] [Table 1]
[0068] In Table 1, when the amount of the IM compound is in the range of more than 0 to 0.3 parts by mass per 100 parts by mass of the composite particles, the resistance increase rate tends to be low. When the amount of the IM compound is in the range of 0.05 to 0.1 parts by mass, the resistance increase rate tends to be further reduced.
[0069] [Table 2]
[0070] In Table 2 above, it can be seen that the larger the BET ratio after the composite treatment, the lower the resistance increase rate. [Explanation of symbols]
[0071] 110 first electrode, 120 second electrode, 130 separator layer, 150 power generating element, 200 all-solid-state battery.
Claims
1. 100 parts by weight of composite particles; 0.05 to 0.103 parts by mass of an imidazoline compound; Including, The composite particle includes a core particle and a coating layer, the coating layer covers at least a part of the surface of the core particle, The core particle includes an active material, the coating layer includes a fluoride solid electrolyte, The ratio of the specific surface area of the composite particle to the specific surface area of the core particle is 1.50 to 1.
80. Electrodes for all-solid-state batteries.
2. Further comprising 10 to 100 parts by mass of a sulfide solid electrolyte; The electrode for an all-solid-state battery according to claim 1 .
3. The imidazoline compound has the formula (1): 【Chemistry 1】 is represented by In the formula (1), R 1 is an alkyl or hydroxyalkyl group having 1 to 22 carbon atoms; R 2 is an alkyl or alkenyl group having 10 to 22 carbon atoms; The electrode for an all-solid-state battery according to claim 1 or 2.
4. The fluoride solid electrolyte has the formula (2): <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 3-x <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> F<h2 style=";text-align:left;direction:ltr"> 6 <h2 style=";text-align:left;direction:ltr"> …(2) is represented by In the formula (2), x satisfies 0≦x≦1. The electrode for an all-solid-state battery according to claim 1 or 2.
Citation Information
Patent Citations
Coated positive electrode active material for lithium ion battery
JP2018137222A
All-solid-state lithium secondary battery and manufacturing method thereof
JP2020161364A
Positive electrode material, and battery
WO2021187391A1
Positive electrode material and battery
WO2022004397A1
